Do Adolescents Engage in Delinquency to Cope with Depressive Symptoms? Revisiting the Longitudinal Link Between Delinquency and Depressive Symptoms While Considering Moderation by Ethnicity, Adolescent Phase, and Gender - Defoe, Ivy N. (Journal of developmental and life-course criminology, 2023)
The co-occurrence between delinquency and depression in adolescence is well-documented. However, Psychology (Failure model and Acting out Model) and Criminology (Strain Theory) theories are divided on the potential longitudinal link between these two behaviors and empirical studies show mixed findings. The present 3-wave longitudinal study tested these opposing theories, using cross-lagged panel modeling on an ethnically and socio-economically diverse sample (T1: N=602; Mage= 13.50 (SD = 1.23); 46.4% female). Furthermore, we investigated whether moderation by ethnicity (non-Western ethnic minority versus Western ethnic majority [i.e., ethnically Dutch]) or adolescent phase by gender (early adolescent girls versus mid-late adolescent girls versus early adolescent boys versus mid-late adolescent boys) were present. For the total sample, results showed that higher levels of delinquency predicted lower levels of depressive symptoms, consistent with Strain theory that suggests that adolescents may resort to delinquency to cope with depression. As for significant moderation links: (1) higher levels of delinquency predicted lower levels of depressive symptoms (Strain theory), especially in mid-late adolescent girls, (2) higher levels of delinquency predicted higher levels of depressive symptoms (Failure model) for early adolescent girls, and (3) higher levels of depressive symptoms predicted higher levels of delinquency (Acting out model and Strain theory) for mid-late adolescent boys. Although no ethnicity moderation effects were found, consistent with strain theories, ethnic minority adolescents reported significantly more depressive symptoms (T1 and T3) but not higher delinquency levels than ethnic majority adolescents. Thus, the mixed findings found in previous studies for the link between delinquency and depression could be because gender-by-adolescent-phase moderation effects were overlooked. Implications for the Acting out model, Failure model, and Strain theories are discussed.